2010
DOI: 10.1007/s00018-010-0529-x
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of amyloid β(1–40) oligomers into fibrils is characterized by a major change in secondary structure

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder occurring in the elderly. It is widely accepted that the amyloid beta peptide (Ab) aggregation and especially the oligomeric states rather than fibrils are involved in AD onset. We used infrared spectroscopy to provide structural information on the entire aggregation pathway of Ab(1-40), starting from monomeric Ab to the end of the process, fibrils. Our structural study suggests that conversion of oligomers into fibrils results from a transition from ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
122
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(141 citation statements)
references
References 58 publications
18
122
1
Order By: Relevance
“…The ratios of Ab42 (in mM) to SPE product concentration (in mg ml View Online parallel (fibrils) b-sheet content for Ab42 along the aggregation process. 16,34 In support of the current findings, it has been shown that anti-parallel b-sheet structure could also be the signature of toxicity for HET-s(218-289) prion peptide.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…The ratios of Ab42 (in mM) to SPE product concentration (in mg ml View Online parallel (fibrils) b-sheet content for Ab42 along the aggregation process. 16,34 In support of the current findings, it has been shown that anti-parallel b-sheet structure could also be the signature of toxicity for HET-s(218-289) prion peptide.…”
supporting
confidence: 86%
“…33 However, formation of meta-stable oligomeric Ab42 represents an early competing folding pathway 6 characterised by anti-parallel b-sheet structure. 34 In this study, Ab42 preparations modelled the earliest stages of oligomer assembly from aggregate-free stocks 16 over a standard incubation period of 20-24 h.…”
mentioning
confidence: 99%
“…Meanwhile, consistent observations have been reported for different Aβ(1-40) and Aβ(1-42) peptide preparations and for samples from different laboratories. 24,29,71,72 Further, they relate to longstanding evidence on SH3 domain, which produces non-fibrillar aggregates with a well-resolved amide I′ peak at 1684 cm − 1 in D 2 O solution, while no such peak is seen with fibrils. 73 Lysozyme oligomers have also been show to incorporate a peak at 1688 cm − 1 in D 2 O solutions.…”
Section: Role Of Oligomers For the Mechanism Of Fibril Formationmentioning
confidence: 83%
“…43) Structural analyses by isotope-edited Fourier transform IR spectroscopy (FTIR) and solid-state NMR suggested that a toxic form of oligomeric Aβs had anti-parallel β-sheets. 44,45) Furthermore, the fibrils formed on the membrane are significantly cytotoxic, whereas the fibrils formed in solution are less toxic. 13,46) Since the major content of a singly isolated Aβ is α-helix, 47,48) structural transformation into a β-sheet of Aβ will be related to the toxic fibril form.…”
Section: Discussionmentioning
confidence: 99%